The impact of US sugar prices on the financial performance of US sugar-using firms - Carlos J. O. Trejo-Pech; Karen L. DeLong; Dayton M. Lambert; Vasileios Siokos (Agricultural and Food Economics, 2020)
The effect of the United States (US) sugar program on sugar-using firm profitability from 2000 to 2017 is examined using firm financial data and the relative US-to-world sugar price ratio. Return on assets and market-to-book ratio proxy for firm financial performance. The regression results provide statistical evidence that as the US sugar price increases relative to the world sugar price, sugar-using firm financial performance improves. This is likely a result of sugar-using firms passing higher sugar costs on to consumers. An ex post analysis indicates that the statistical tests have adequate power. Findings provide guidelines for future analyses investigating the relationship between the US sugar program and sugar-using firm financial performance.
Keywords: 330; Agribusiness finance; Sugar-using firms; US sugar program; Power of test